Nanoporous fuel cell catalyst and preparation method thereof

By preparing a fuel cell catalyst with a nanoporous structure, using the combination of modified filler and mixed support, the problem of low catalytic efficiency caused by low space contact surface in the prior art is solved, and a more efficient catalytic effect and platinum utilization rate is achieved.

CN116805694BActive Publication Date: 2025-04-01LUOHYDROGEN NEW MATERIAL TECH (GUANGDONG) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310748308.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2025-04-01
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

The spatial contact surface of existing fuel cell catalysts is low, resulting in low overall catalytic efficiency, and the accumulation of catalysts is prone to waste of platinum catalysts.

Method used

The nanoporous fuel cell catalyst is used, and the preparation method includes preparing modified fillers and mixed support, preparing modified fillers through materials such as nanoalumina, n-butyl titanate, γ-aminopropyltriethoxysilane, and preparing mixed support through materials such as graphene oxide, epoxy soybean oil, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, and finally loading platinum on the support to form a nanoporous structure to improve the spatial contact surface.

Benefits of technology

By increasing the space contact surface, the overall catalytic efficiency of fuel cell catalysts is significantly improved and the waste of platinum catalysts is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004300374990000061
    Figure BDA0004300374990000061
  • Figure BDA0004300374990000062
    Figure BDA0004300374990000062
  • Figure BDA0004300374990000072
    Figure BDA0004300374990000072
Patent Text Reader

Abstract

The invention discloses a nanoporous fuel cell catalyst and a preparation method thereof, which includes the following raw materials: a mixed carrier, a chloroplatinic acid solution, and a surfactant; the mixed carrier includes the following raw materials: graphene oxide, ethylene glycol, deionized water, a modified filler, epoxy soybean oil, γ-(2,3-glycidoxy)propyltrimethoxysilane, acetic acid, and a hydrazine hydrate solution; the modified filler includes the following raw materials: nano alumina, n-butyl titanate, ethanol, deionized water, and γ-aminopropyltriethoxysilane. Platinum is loaded on the mixed carrier to form a nanoporous fuel cell catalyst, and graphene oxide is accessed to epoxy soybean oil and γ-(2,3-glycidoxy)propyltrimethoxysilane through the surface to increase its spatial distribution, and the raw materials are evenly distributed, thereby increasing the spatial distribution of the mixed carrier, increasing the carrying capacity of platinum in the mixed carrier, and increasing the spatial contact area to improve the overall catalytic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to a nanoporous fuel cell catalyst and a preparation method thereof. Background Art

[0002] The main components of a proton exchange membrane fuel cell (PEMFC) are: proton exchange membrane / electrode assembly (MEA), gas diffusion layer, and bipolar plate. In a proton exchange membrane fuel cell, hydrogen enters the anode and contacts the catalyst to promote the separation of hydrogen into hydrogen ions (protons) and electrons. Electrons enter the cathode through the circuit, and hydrogen ions enter the cathode through the membrane / electrolyte. Oxygen enters the cathode, and with the help of the catalyst, it combines with hydrogen ions and electrons to form water; the catalyst is an important component of a proton exchange membrane fuel cell.

[0003] In the prior art, platinum catalyst is selected as one of the important components of the catalytic assembly, but the distribution of the catalyst has a great influence on the catalytic effect. When the spatial contact area is low, the overall catalytic efficiency is not high; at the same time, the accumulation of the catalyst is also likely to cause waste of platinum catalyst.

[0004] In summary, after extensive searching by the applicant, it is found that there is at least a technical problem in this field that the overall catalytic efficiency is low when the spatial contact surface is low. Therefore, it is necessary to develop or improve a nanoporous fuel cell catalyst and a preparation method thereof. Summary of the invention

[0005] Based on this, in order to solve the problem of low overall catalytic efficiency when the spatial contact surface is low, the present invention provides a nanoporous fuel cell catalyst and a preparation method thereof. The specific technical scheme is as follows:

[0006] A nanoporous fuel cell catalyst, comprising the following raw materials by weight: 25-30 parts of a mixed carrier, 68-72 parts of a chloroplatinic acid solution, and 2-4 parts of a surfactant;

[0007] The mixed carrier comprises the following raw materials: 12-18 parts of graphene oxide, 18-22 parts of ethylene glycol, 43-48 parts of deionized water, 4-6 parts of modified filler, 2-4 parts of epoxy soybean oil, 4-6 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 2-3 parts of acetic acid, and 4-6 parts of hydrazine hydrate solution;

[0008] The modified filler comprises the following raw materials: 8-12 parts of nano-alumina, 4-6 parts of n-butyl titanate, 23-27 parts of ethanol, 52-58 parts of deionized water, and 4-6 parts of gamma-aminopropyltriethoxysilane.

[0009] Furthermore, the nanoporous fuel cell catalyst comprises the following preparation raw materials, calculated by weight: 27 parts of a mixed carrier, 70 parts of a chloroplatinic acid solution, and 3 parts of a surfactant;

[0010] The mixed carrier comprises the following raw materials: 15 parts of graphene oxide, 20 parts of ethylene glycol, 45 parts of deionized water, 5 parts of modified filler, 3 parts of epoxy soybean oil, 5 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 2 parts of acetic acid, and 5 parts of hydrazine hydrate solution;

[0011] The modified filler comprises the following raw materials: 10 parts of nano-alumina, 5 parts of n-butyl titanate, 25 parts of ethanol, 55 parts of deionized water, and 5 parts of gamma-aminopropyltriethoxysilane.

[0012] Furthermore, the surfactant is polydiallyldimethylammonium chloride.

[0013] The present technical solution also provides a method for preparing a nanoporous fuel cell catalyst, comprising the following preparation steps:

[0014] Preparation of modified filler: Nano-alumina is dispersed in a mixture of deionized water and ethanol for 10-15 minutes, n-butyl titanate is added after dispersion is completed, a premix is ​​obtained after addition is completed, the premix is ​​dried, and after drying, γ-aminopropyltriethoxysilane is sprayed on the surface of the premix to obtain a modified filler;

[0015] Preparation of mixed carrier: ultrasonically disperse graphene oxide in a mixed solution formed by ethylene glycol solution and deionized water for 5 min-10 min, and add modified filler, epoxy soybean oil, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and acetic acid and ultrasonically disperse for 30 min-35 min; after dispersion, add hydrazine hydrate solution for mixed dispersion, adjust the pH to 8-9, wash and dry after mixed dispersion to obtain a mixed carrier;

[0016] The catalyst is loaded on the carrier; the mixed carrier is dispersed in a chloroplatinic acid solution; after adding a surfactant, the dispersion is continued for 15 minutes to 20 minutes; after the dispersion is completed, the catalyst is filtered and reduced to obtain a nanoporous fuel cell catalyst.

[0017] Furthermore, the chloroplatinic acid solution is a chloroplatinic acid solution with a mass fraction of 1%.

[0018] Furthermore, the method of adding n-butyl titanate is to drop n-butyl titanate in a dispersed state, the dropping time is 5 min-10 min, and after the dropping is completed, the dispersion is continued for 15 min-20 min.

[0019] Furthermore, the drying process in the preparation of the modified filler is specifically drying at 80° C.-90° C. for 20 min-25 min.

[0020] Furthermore, the adding of hydrazine hydrate solution for mixing and dispersing is specifically carried out by ultrasonic dispersion at 110° C. for 35 min-40 min.

[0021] Furthermore, the washing and drying treatment of the mixed carrier preparation is specifically washing with water for 2 minutes to 3 minutes and then drying at 60° C. to 70° C. for 30 minutes to 40 minutes.

[0022] Furthermore, the reduction treatment in the carrier-supported catalyst is specifically carried out by introducing hydrogen at 100° C.-150° C.

[0023] In the above technical scheme, platinum is loaded on a mixed carrier to form a nanoporous fuel cell catalyst, wherein the mixed carrier is mainly prepared by graphene oxide, modified filler, epoxy soybean oil, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane. Graphene oxide is connected to epoxy soybean oil and γ-(2,3-epoxypropoxy)propyltrimethoxysilane through the surface to increase its spatial distribution, and is mixed with the modified filler. The raw materials are evenly distributed, the spatial distribution of the mixed carrier is increased, the platinum loading capacity on the mixed carrier is increased, and the spatial contact area is increased to improve the overall catalytic efficiency. In addition, the modified filler The filler is mainly prepared by nano-alumina, n-butyl titanate and γ-aminopropyltriethoxysilane. The nano-alumina is dried after adding n-butyl titanate, so that titanium dioxide is attached to the surface of the nano-alumina, which increases its spatial contact area and provides a good prerequisite for the mixed carrier to form a larger spatial distribution. At the same time, the surface is modified by γ-aminopropyltriethoxysilane to provide the surface of the modified filler with amino groups that react with graphene oxide, thereby improving the uniformity of the distribution of the modified filler and graphene oxide, improving the spatial distribution and stability of the mixed carrier, and increasing the spatial contact area, thereby improving the overall catalytic efficiency. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0026] A nanoporous fuel cell catalyst in one embodiment of the present invention includes the following raw materials, calculated by weight: 25-30 parts of a mixed carrier, 68-72 parts of a chloroplatinic acid solution, and 2-4 parts of a surfactant;

[0027] The mixed carrier comprises the following raw materials: 12-18 parts of graphene oxide, 18-22 parts of ethylene glycol, 43-48 parts of deionized water, 4-6 parts of modified filler, 2-4 parts of epoxy soybean oil, 4-6 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 2-3 parts of acetic acid, and 4-6 parts of hydrazine hydrate solution;

[0028] The modified filler comprises the following raw materials: 8-12 parts of nano-alumina, 4-6 parts of n-butyl titanate, 23-27 parts of ethanol, 52-58 parts of deionized water, and 4-6 parts of gamma-aminopropyltriethoxysilane.

[0029] In one embodiment, the nanoporous fuel cell catalyst includes the following preparation raw materials, calculated by weight: 27 parts of mixed carrier, 70 parts of chloroplatinic acid solution, and 3 parts of surfactant;

[0030] The mixed carrier comprises the following raw materials: 15 parts of graphene oxide, 20 parts of ethylene glycol, 45 parts of deionized water, 5 parts of modified filler, 3 parts of epoxy soybean oil, 5 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 2 parts of acetic acid, and 5 parts of hydrazine hydrate solution;

[0031] The modified filler comprises the following raw materials: 10 parts of nano-alumina, 5 parts of n-butyl titanate, 25 parts of ethanol, 55 parts of deionized water, and 5 parts of gamma-aminopropyltriethoxysilane.

[0032] In one embodiment, the surfactant is polydiallyldimethylammonium chloride.

[0033] The present technical solution also provides a method for preparing a nanoporous fuel cell catalyst, comprising the following preparation steps:

[0034] Preparation of modified filler: Nano-alumina is dispersed in a mixture of deionized water and ethanol for 10-15 minutes, n-butyl titanate is added after dispersion is completed, a premix is ​​obtained after addition is completed, the premix is ​​dried, and after drying, γ-aminopropyltriethoxysilane is sprayed on the surface of the premix to obtain a modified filler;

[0035] Preparation of mixed carrier: ultrasonically disperse graphene oxide in a mixed solution formed by ethylene glycol solution and deionized water for 5 min-10 min, and add modified filler, epoxy soybean oil, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and acetic acid and ultrasonically disperse for 30 min-35 min; after dispersion, add hydrazine hydrate solution for mixed dispersion, adjust the pH to 8-9, wash and dry after mixed dispersion to obtain a mixed carrier;

[0036] The catalyst is loaded on the carrier; the mixed carrier is dispersed in a chloroplatinic acid solution; after adding a surfactant, the dispersion is continued for 15 minutes to 20 minutes; after the dispersion is completed, the catalyst is filtered and reduced to obtain a nanoporous fuel cell catalyst.

[0037] In one embodiment, the chloroplatinic acid solution is a chloroplatinic acid solution with a mass fraction of 1%.

[0038] In one of the embodiments, the method of adding n-butyl titanate is to drop n-butyl titanate in a dispersed state, the dropping time is 5min-10min, and after the dropping is completed, the dispersion is continued for 15min-20min.

[0039] In one of the embodiments, the drying process in the preparation of the modified filler is specifically drying at 80° C.-90° C. for 20 min-25 min.

[0040] In one embodiment, the adding of hydrazine hydrate solution for mixing and dispersing is specifically ultrasonic dispersion at 110° C. for 35 min-40 min.

[0041] In one of the embodiments, the washing and drying treatment of the mixed carrier preparation is specifically washing for 2 minutes to 3 minutes and then drying at 60° C. to 70° C. for 30 minutes to 40 minutes.

[0042] In one embodiment, the reduction treatment of the carrier-supported catalyst is carried out by introducing hydrogen at 100° C.-150° C.

[0043] In one embodiment, the hydrazine hydrate solution is an aqueous solution of hydrazine hydrate with a mass fraction of 80%.

[0044] In one embodiment, the nano-alumina is specifically modeled as VK-L10Y, has a white powder appearance, a γ-phase crystal form, a particle size of 10 nm, a content of 99.99%, and a specific surface area of ​​180-220 m 2 / g of nano alumina.

[0045] In one embodiment, ammonia water is used to adjust the pH to 8-9.

[0046] In one embodiment, the hydrogen gas flow rate is 0.5 L / s-1 L / s.

[0047] In one embodiment, the addition of hydrazine hydrate solution is used for reduction treatment.

[0048] The embodiments of the present invention will be described in detail below with reference to specific examples.

[0049] The difference between Examples 1-4 and Comparative Examples 1-5 is that the addition amount of the raw materials is different, and the preparation process is the same, as shown in Table 1-3.

[0050] Table 1 Raw materials for preparing modified fillers:

[0051]

[0052] Table 2 Raw materials for mixed carrier preparation

[0053]

[0054]

[0055] Table 3 Raw materials for preparation of carrier-supported catalyst

[0056]

[0057] The nano-alumina is specifically modeled as VK-L10Y, has the appearance of white powder, a γ-phase crystal form, a particle size of 10 nm, a content of 99.99%, and a specific surface area of ​​180-220 m 2 / g of nano-alumina; the hydrazine hydrate solution is an aqueous solution of hydrazine hydrate with a mass fraction of 80%; and the surfactant is polydiallyldimethylammonium chloride.

[0058] The specific preparation process is as follows:

[0059] A method for preparing a nanoporous fuel cell catalyst comprises the following steps:

[0060] Preparation of modified filler: Nano-alumina is dispersed in a mixture of deionized water and ethanol for 15 minutes. After dispersion, n-butyl titanate is added. Specifically, n-butyl titanate is added dropwise in a dispersed state for 10 minutes. After the addition is completed, dispersion is continued for 20 minutes. After the addition is completed, a premix is ​​obtained, and the premix is ​​dried at 80°C for 20 minutes to 25 minutes. After the drying process is completed, γ-aminopropyltriethoxysilane is sprayed on the surface of the premix to obtain a modified filler;

[0061] Preparation of mixed carrier; ultrasonically disperse graphene oxide in a mixed solution of ethylene glycol solution and deionized water for 5min-10min, and add modified filler, epoxy soybean oil, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and acetic acid and ultrasonically disperse for 35min; after dispersion, add hydrazine hydrate solution and ultrasonically disperse for 40min at 110°C. The purpose of adding hydrazine hydrate solution is to perform reduction treatment. Ammonia water is used to adjust the pH to 8-9. After the mixed dispersion is completed, wash with water for 2min-3min and dry at 60℃-70℃ for 30min-40min. Obtain a mixed carrier;

[0062] The catalyst is loaded on the carrier; the mixed carrier is dispersed in a chloroplatinic acid solution; the surfactant is added and the dispersion is continued for 20 minutes; the dispersion is completed and filtered, and the nanoporous fuel cell catalyst is obtained after the filtration is completed. The reduction treatment in the catalyst loaded on the carrier is specifically carried out by introducing hydrogen at 150° C., and the hydrogen introduction flow rate is 1 L / s.

[0063] The fuel cell catalysts prepared in Examples 1-4 and Comparative Examples 1-5 were subjected to relevant performance tests, and the results are shown in Table 4, wherein the catalytic activity is measured by the conversion rate of fuel oxygen, which is the conversion rate calculated by introducing the same amount of raw material under the same amount of platinum catalyst.

[0064] Table 4:

[0065]

[0066] It can be seen from the data in Table 4 that the nanoporous fuel cell catalysts prepared in Examples 1-4 have good catalytic activity, and can solve the technical problem of low overall catalytic efficiency in the case of low spatial contact surface in the prior art; specifically, the difference between Comparative Example 1 and Example 1 is that n-butyl titanate is not added in the preparation of the modified filler in the catalyst prepared in Comparative Example 1. It can be seen from the data in Table 4 that the catalytic activity of the catalyst prepared in Comparative Example 1 is not as good as the catalytic activity of the nanoporous fuel cell catalyst prepared in Example 1, which shows that the modified filler prepared by adding n-butyl titanate has a positive effect on the catalytic activity of the fuel cell catalyst. The addition of n-butyl titanate coats the surface of nano-alumina with titanium dioxide, makes the specific surface area of ​​nano-alumina wider, improves the spatial extension, and has a positive effect on the formed mixed carrier having a larger specific surface area, thereby improving the overall catalytic efficiency;

[0067] The difference between Comparative Example 2 and Example 1 is that γ-aminopropyltriethoxysilane is not added in the preparation of the modified filler in the catalyst prepared in Comparative Example 2. It can be seen from the data in Table 4 that the catalytic activity of the catalyst prepared in Comparative Example 2 is inferior to the catalytic activity of the nanoporous fuel cell catalyst prepared in Example 1. It can be seen that the addition of γ-aminopropyltriethoxysilane has a positive effect on the catalytic activity of the fuel cell catalyst. The addition of γ-aminopropyltriethoxysilane allows the nano-alumina coated with titanium dioxide to be dispersed synchronously with the subsequent graphene oxide, improves the uniformity of dispersion, and increases the degree of dendritic distribution of graphene and the modified filler. It has a positive effect on the formed mixed carrier having a larger specific surface area, thereby improving the overall catalytic efficiency;

[0068] The difference between Comparative Example 3 and Example 1 is that no modified filler is added to the catalyst prepared in Comparative Example 3. From the data in Table 4, it can be seen that the catalytic activity of the catalyst prepared in Comparative Example 3 is not as good as the catalytic activity of the nanoporous fuel cell catalyst prepared in Example 1. It can be seen that the catalytic activity of the nanoporous fuel cell can be effectively improved by adding a modified filler, so that the graphene oxide and the modified filler form a dendrite distribution, which has a positive effect on the formed mixed carrier having a larger specific surface area, thereby improving the overall catalytic efficiency;

[0069] The difference between Comparative Example 4 and Example 1 is that no epoxy soybean oil is added to the mixed carrier in the catalyst prepared in Comparative Example 4. It can be seen from the data in Table 4 that the catalytic activity of the catalyst prepared in Comparative Example 4 is inferior to the catalytic activity of the nanoporous fuel cell catalyst prepared in Example 1. It can be seen that the catalytic activity of the nanoporous fuel cell can be effectively improved by adding epoxy soybean oil. The epoxy soybean oil is added to modify the surface of the graphene oxide in the mixed carrier to improve the spatial extension. At the same time, it is dispersed with the modified filler under the action of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to form a dendritic distribution, which has a positive effect on the formed mixed carrier having a larger specific surface area, thereby improving the overall catalytic efficiency;

[0070] The difference between Comparative Example 5 and Example 1 is that γ-(2,3-epoxypropoxy)propyltrimethoxysilane is not added to the mixed carrier of the catalyst prepared in Comparative Example 5. It can be seen from the data in Table 4 that the catalytic activity of the catalyst prepared in Comparative Example 5 is inferior to the catalytic activity of the nanoporous fuel cell catalyst prepared in Example 1. It can be seen that the mixed carrier of γ-(2,3-epoxypropoxy)propyltrimethoxysilane has a positive effect on the overall catalytic efficiency of the prepared nanoporous fuel cell catalyst. The addition of γ-(2,3-epoxypropoxy)propyltrimethoxysilane allows the modified filler and graphene oxide to be cross-linked with each other, thereby increasing the spatial distribution ductility, thereby having more contact space, thereby achieving the effect of improving the overall catalytic efficiency.

[0071] Platinum is loaded on a mixed carrier to form a nanoporous fuel cell catalyst, wherein the mixed carrier is mainly prepared by graphene oxide, modified filler, epoxy soybean oil, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane. Graphene oxide is connected to epoxy soybean oil and γ-(2,3-epoxypropoxy)propyltrimethoxysilane through the surface to increase its spatial distribution, and is mixed with the modified filler. The raw materials are evenly distributed, the spatial distribution of the mixed carrier is increased, the platinum loading capacity on the mixed carrier is increased, and the spatial contact area is increased to improve the overall catalytic efficiency. In addition, the modified filler is mainly The invention is prepared by nano-alumina, n-butyl titanate and γ-aminopropyltriethoxysilane. The nano-alumina is dried after adding n-butyl titanate, so as to obtain titanium dioxide attached to the surface of the nano-alumina, thereby increasing its spatial contact surface and providing a good prerequisite for the mixed carrier to form a larger spatial distribution. At the same time, the surface is modified by γ-aminopropyltriethoxysilane to provide the surface of the modified filler with amino groups that react with graphene oxide, thereby improving the uniformity of the distribution of the modified filler and graphene oxide, improving the spatial distribution and stability of the mixed carrier, and increasing the spatial contact surface, thereby improving the overall catalytic efficiency.

[0072] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0073] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A nanoporous fuel cell catalyst, characterized in that: The preparation raw materials include the following by weight: 25-30 parts of mixed carrier, 68-72 parts of chloroplatinic acid solution, and 2-4 parts of surfactant; The mixed carrier comprises the following raw materials: 12-18 parts of graphene oxide, 18-22 parts of ethylene glycol, 43-48 parts of deionized water, 4-6 parts of modified filler, 2-4 parts of epoxy soybean oil, 4-6 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 2-3 parts of acetic acid, and 4-6 parts of hydrazine hydrate solution; The modified filler comprises the following raw materials: 8-12 parts of nano-alumina, 4-6 parts of n-butyl titanate, 23-27 parts of ethanol, 52-58 parts of deionized water, and 4-6 parts of γ-aminopropyltriethoxysilane; The surfactant is polydiallyldimethylammonium chloride.

2. The nanoporous fuel cell catalyst according to claim 1, characterized in that: The nanoporous fuel cell catalyst comprises the following preparation raw materials by weight: 27 parts of mixed carrier, 70 parts of chloroplatinic acid solution, and 3 parts of surfactant; The mixed carrier comprises the following raw materials: 15 parts of graphene oxide, 20 parts of ethylene glycol, 45 parts of deionized water, 5 parts of modified filler, 3 parts of epoxy soybean oil, 5 parts of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 2 parts of acetic acid, and 5 parts of hydrazine hydrate solution; The modified filler comprises the following raw materials: 10 parts of nano-alumina, 5 parts of n-butyl titanate, 25 parts of ethanol, 55 parts of deionized water, and 5 parts of gamma-aminopropyltriethoxysilane.

3. A method for preparing a nanoporous fuel cell catalyst, characterized in that: The method comprises the following preparation steps: Preparation of modified filler: Nano-alumina is dispersed in a mixture of deionized water and ethanol for 10-15 minutes, n-butyl titanate is added after dispersion is completed, a premix is ​​obtained after addition is completed, the premix is ​​dried, and after drying, γ-aminopropyltriethoxysilane is sprayed on the surface of the premix to obtain a modified filler; Preparation of mixed carrier: ultrasonically disperse graphene oxide in a mixed solution formed by ethylene glycol solution and deionized water for 5 min-10 min, and add modified filler, epoxy soybean oil, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and acetic acid and ultrasonically disperse for 30 min-35 min; after dispersion, add hydrazine hydrate solution for mixed dispersion, adjust the pH to 8-9, wash and dry after mixed dispersion to obtain a mixed carrier; The catalyst is loaded on the carrier; the mixed carrier is dispersed in a chloroplatinic acid solution; after adding a surfactant, the dispersion is continued for 15 minutes to 20 minutes, and the surfactant is polydiallyldimethylammonium chloride; after the dispersion is completed, the catalyst is filtered and reduced to obtain a nanoporous fuel cell catalyst.

4. The method for preparing a nanoporous fuel cell catalyst according to claim 3, characterized in that: The chloroplatinic acid solution is a chloroplatinic acid solution with a mass fraction of 1%.

5. The method for preparing a nanoporous fuel cell catalyst according to claim 3, characterized in that: The method of adding n-butyl titanate is to drop n-butyl titanate in a dispersed state, the drop adding time is 5 min-10 min, and the dispersion is continued for 15 min-20 min after the drop adding is completed.

6. The method for preparing a nanoporous fuel cell catalyst according to claim 3, characterized in that: The drying treatment in the preparation of the modified filler is specifically drying at 80° C.-90° C. for 20 min-25 min.

7. The method for preparing a nanoporous fuel cell catalyst according to claim 3, characterized in that: The adding of hydrazine hydrate solution for mixing and dispersing is specifically carried out by ultrasonic dispersion at 110° C. for 35 min-40 min.

8. The method for preparing a nanoporous fuel cell catalyst according to claim 3, characterized in that: The washing and drying treatment of the mixed carrier preparation is specifically washing with water for 2 minutes to 3 minutes and then drying at 60° C. to 70° C. for 30 minutes to 40 minutes.

9. The method for preparing a nanoporous fuel cell catalyst according to claim 3, characterized in that: The reduction treatment of the carrier-supported catalyst is specifically carried out by introducing hydrogen at 100° C.-150° C.

Citation Information

Patent Citations

  • Platinum / graphene nano electro-catalyst and preparation method thereof

    CN101745384A

  • Graphene catalyst

    CN105355823A